2021
DOI: 10.1016/j.jviromet.2021.114153
|View full text |Cite
|
Sign up to set email alerts
|

Accessioning and automation compatible anterior nares swab design

Abstract: The COVID-19 pandemic has resulted in an unparalleled need for viral testing capacity across the world and is a critical requirement for successful re-opening of economies. The logistical barriers to near-universal testing are considerable. We have designed an injection molded polypropylene anterior nares swab, the Rhinostic, with a screw cap integrated into the swab handle that is compatible with fully automated sample accessioning and processing. The ability to collect and release both human and viral materi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 11 publications
4
20
0
Order By: Relevance
“…As expected, our data show a higher absorption capacity for these flocked swabs (S4, S5, and S7) compared to other cotton fiber ones, but still less than for the Ca-alginate swab (S6; Table 1 ). The total amount of absorbed liquid is similar in both types of flocked swabs and is comparable with data reported in the literature ( 35 , 36 ). These data should ultimately be compared with matrices usually collected in the field, in order to estimate the variation in the swabs’ absorption capacities.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As expected, our data show a higher absorption capacity for these flocked swabs (S4, S5, and S7) compared to other cotton fiber ones, but still less than for the Ca-alginate swab (S6; Table 1 ). The total amount of absorbed liquid is similar in both types of flocked swabs and is comparable with data reported in the literature ( 35 , 36 ). These data should ultimately be compared with matrices usually collected in the field, in order to estimate the variation in the swabs’ absorption capacities.…”
Section: Discussionsupporting
confidence: 89%
“…These flocked swabs (S4 and S5) contain long nylon fibers embedded in a hydrophilic layer, which provides better capillary action and stronger hydraulic uptake of liquids. The new tip design may increase the absorption of targeted cells by 2- to 3-fold over traditional rayon-tipped swabs and improves diagnostic sensitivity ( 35 ). The use of flocked swabs was also reported to enhance the efficiency of bacterium recovery and DNA detection compared to traditional fibers ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…New swab production methods have been explored to address the increase in demand for nasal swabs. 3D printed and injected molded swabs displayed performance comparable to standard flocked swabs (4,8), while offering high throughput, cost effective alternatives (8,9). In addition, a non-absorbent swab would allow to collected samples in limited volumes and to elute them into smaller volume of transport media, in comparison to standard absorbent swab, resulting in greater sample concentration and subsequent increase in sensitivity in viral RNA detection.…”
Section: Introductionmentioning
confidence: 99%
“…To support our model as a suitable tool for swab validation, we developed and performed several assays to assess swab pick up and release efficiencies and then evaluate data agreement against available literature. In addition, an in vitro tissue model would provide more controlled experimental conditions, in comparison to clinical studies that have shown greater variability, arising from differences in sampling methods, nasal cavity structure, nasal fluid viscosity, and other conditions that vary from patient to patient and season to season [3][4] . Moreover, the disadvantages of relying on clinical trials for initial swab validation are also the bureaucratic aspects (i.e., recruitment, regulatory requirements, and cost).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to a standard flocked, the injectionmolded swabs are characterized by a non-absorbent head, and have demonstrated a more efficient release of viral RNA while absorbing less solution 1, 4-5 . As a result, several prototypes of injectionmolded swabs have been recently commercialized, including nasopharyngeal and mid-turbinate swabs like the IM2 and Rhinostic swabs [3][4] . These new one-piece specimen collection swabs can be efficiently mass produced, without multistep manufacturing methods, and post-processing.…”
Section: Text Introductionmentioning
confidence: 99%